Functional role of CD44v‐xCT system in the development of spasmolytic polypeptide‐expressing metaplasia. Issue 10 (12th August 2013) - Wada, Takeyuki; Ishimoto, Takatsugu; Seishima, Ryo; Tsuchihashi, Kenji; Yoshikawa, Momoko; Oshima, Hiroko; Oshima, Masanobu; Masuko, Takashi; Wright, Nicholas A.; Furuhashi, Satoshi; Hirashima, Kotaro; Baba, Hideo; et al.
Abstract : Cancer development is often preceded by the appearance of preneoplastic lesions. In gastric carcinogenesis, chronic inflammation and histopathologic progression of the stomach epithelium lead to the development of metaplasia and eventually adenocarcinoma. The cell surface protein CD44, especially its variant isoforms (CD44v), has been implicated in metaplasia–carcinoma sequence progression in the stomach. We recently found that CD44v interacts with and stabilizes xCT, a subunit of the cystine transporter system xc(–), in cancer cells and thereby increases cystine uptake and confers resistance to various types of cellular stress in vivo . The functional relevance of CD44v and xCT in the development of preneoplastic lesions, however, has remained unknown. We have now examined the role of the CD44v‐xCT system in the development of spasmolytic polypeptide‐expressing metaplasia (SPEM) in mouse models of gastric carcinogenesis. CD44v was found to be expressed de novo in SPEM, and CD44v + metaplastic cells manifested upregulation of xCT expression compared with CD44v − cells. Genetic ablation of CD44 or treatment with sulfasalazine, an inhibitor of xCT‐dependent cystine transport, suppressed the development of SPEM and subsequent gastric tumor growth. Therapy targeted to CD44v‐xCT could thus prove effective for prevention or attenuation of the CD44v‐dependent development of preneoplastic lesions and cancer.